2011
DOI: 10.3221/igf-esis.19.05
|View full text |Cite
|
Sign up to set email alerts
|

Micro void coalescence of ductile fracture in mild steel during tensile straining

Abstract: ABSTRACT. The ductile fracture occurs mainly in three stages i.e. void nucleation, void growth and the void coalescence. The present work focuses on the study the coalescence of existing micro void in a ductile material, mild steel. The specimen with holes in square array at various angle to load axis have been tested. The holes were machined in the specimen and assuming those hole as the voids. The growth and coalescence behaviours during tensile straining were observed both in macro and micro levels. Since t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Comparing Figure 11b-e, the dimple size in the horizontal samples (numbers 3, 6, and 8) were found to be similar to that in the vertical sample (number 11). Due to the micro-void coalescence effect [28], some large dimples appeared locally.…”
Section: Fractographymentioning
confidence: 99%
“…Comparing Figure 11b-e, the dimple size in the horizontal samples (numbers 3, 6, and 8) were found to be similar to that in the vertical sample (number 11). Due to the micro-void coalescence effect [28], some large dimples appeared locally.…”
Section: Fractographymentioning
confidence: 99%
“…It was found that the specimen exhibits ductile fracture, where the fracture surface shows moderate necking before the break which is shown in Figure 4. The nature of ductile fracture is associated with a large amount of plastic deformation and occurs when the total stress (the sum of local stress, flow stress and hydrostatic stress) exceeds the interface bond strength [20]. The ultimate tensile strength is used as an indicator of a material limit stress at which the input parameters for the cyclic test.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the microhardness varies between 270 HV and 260 HV when measured near the top part. Generally, the deposited material goes through complex thermal cycles, which is expected to affect the microhardness [26,27]. It has been confirmed that the fluctuation of the microhardness comes from various thermal cycles and cooling rates in diverse parts of the component, and the microhardness values of multilayers are influenced by the heating at previous layers [28].…”
Section: Microhardnessmentioning
confidence: 90%